Felicia, the political memoirs of Don Dunstan. - Dunstan, Don, 1926-1999. (South Melbourne : Macmillan, 1981)
Includes brief discussion of policy on law reform for Aborigines, land rights, Point Pearce and Pitjantjatjara.
Includes index.
Keywords: Dunstan, Don, -- 1926-1999.; South Australia. Dunstan, Don. Biographies; Statesmen -- South Australia -- Biography; Pitjantjatjara people (C6) (NT SG52-11); Government policy - Assimilation - 1951-1971.; Land rights; Government policy - State and territory - South Australia; South Australia -- Politics and government -- 1965-; Bookayana / Point Pearce (SE SA SI53-12)